Analysis of Coherence and Cohesion in Paragraphs Writing of EFL Students - Agustini, Made Ari Dwita; Ramendra, Dewa Putu; Adnyani, Luh Putu Sri (Journal of Educational Study, 2025)
This study examines coherence and cohesion in paragraphs written by high school students learning English as a Foreign Language (EFL). Employing an explanatory sequential mixed-method design, data were gathered through cluster random sampling, with one class selected as the study sample. The students’ recount paragraphs were analyzed using both quantitative scoring and qualitative content analysis to capture a comprehensive understanding of their writing skills within the EFL context. The results revealed a high level of coherence, with an average score of 83, indicating that students were able to organize ideas logically and connect sentences clearly. These findings underscore the critical role of EFL educators in developing students’ mastery of coherence and cohesion, which are essential for effective writing. The study highlights the importance of teachers possessing strong evaluative skills to identify strengths and weaknesses in student writing, thereby enabling targeted instruction that can enhance writing proficiency in EFL settings.